Factores de Riesgo y De Protección Asociados al Bullying Presentes en Estudiantes de 7° Grado de Bachillerato de La Institución Educativa Distrital Unión Europea Sede A de la Ciudad De Bogotá (2014)
This piece of research is aimed to describe the factors of risk and protection related to Bullying in 7th graders at Institucion Educativa Distrital Unión Europea Sede A. The project provides the theoretical concepts about Bullying and Aggression given by Olweus (1998) and the factors of risk and protection associated to Bullying. Likewise, concepts given in other research projects - Cajigas, et al. (2006), Loredo, et al. (2008), Del Rey, et al. (2008), García, et al. (2010) y Joffre, et al. (2011)- are presented. For this research project, an instrument called “Factores Asociados al Bullying” was designed and applied to 60 students in order to identify the factors of risk and protection associated with Bullying. This is a descriptive, non-experimental and a transversal study and it allowed me to evidence that the most common factors of risk in the students and at the school were related to the silence towards the intimidation and the students’ tolerance towards aggression. The factors of protection associated with Bullying were the intervention of the family and the school. Finally, the project evidences that the most important factors of students’ reaction towards Bullying are: having friends, feeling protected at home, and attending the school activities with parents.